Limbal stem cell transplantation: current perspectives - Atallah MR (Dove Medical Press, 2016)
Marwan Raymond Atallah, Sotiria Palioura, Victor L Perez, Guillermo Amescua Department of Ophthalmology, Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, Miami, FL, USA Abstract: Regeneration of the corneal surface after an epithelial insult involves division, migration, and maturation of a specialized group of stem cells located in the limbus. Several insults, both intrinsic and extrinsic, can precipitate destruction of the delicate microenvironment of these cells, resulting in limbal stem cell deficiency (LSCD). In such cases, reepithelialization fails and conjunctival epithelium extends across the limbus, leading to vascularization, persistent epithelial defects, and chronic inflammation. In partial LSCD, conjunctival epitheliectomy, coupled with amniotic membrane transplantation, could be sufficient to restore a healthy surface. In more severe cases and in total LSCD, stem cell transplantation is currently the best curative option. Before any attempts are considered to perform a limbal stem cell transplantation procedure, the ocular surface must be optimized by controlling causative factors and comorbid conditions. These factors include adequate eyelid function or exposure, control of the ocular surface inflammatory status, and a well-lubricated ocular surface. In cases of unilateral LSCD, stem cells can be obtained from the contralateral eye. Newer techniques aim at expanding cells in vitro or in vivo in order to decrease the need for large limbal resection that may jeopardize the “healthy” eye. Patients with bilateral disease can be treated using allogeneic tissue in combination with systemic immunosuppressive therapy. Another emerging option for this subset of patients is the use of noncorneal cells such as mucosal grafts. Finally, the use of keratoprosthesis is reserved for patients who are not candidates for any of the aforementioned options, wherein the choice of the type of keratoprosthesis depends on the severity of the disease. In summary, limbal stem cell transplantation improves both vision and quality-of-life in patients with ocular surface disorders associated with LSCD, and overall, the use of autologous tissue offers the best results. Future studies aim at improving cellular expansion and finding different sources of stem cells. Keywords: limbal stem cell deficiency (LSCD), simple limbal epithelial transplantation (SLET), cultivated limbal epithelial transplantation (CLET), keratolimbal allograft (KLAL)